Pensamiento, Pandemia y Big Data El impacto sociocultural del coronavirus en el espacio iberoamericano - Cuiñas, Ana Gallego; Tapias, José Antonio Pérez (Humanidades Digitales y Big Data en Iberoamérica / Digital Humanities and Big Data in Ibero-America, 2022)
This book explores the political, social and cultural consequences of COVID-19 through a corpus of over 15.000 articles published in Spain and Latin America in the first pandemic year. Organized around four epistemic fields (geopolitics, gender, biopolitics, philosophy and culture), the contributions offer a quantitative and qualitative analysis combining Big Data tools and humanistic thought.